2014
DOI: 10.1016/j.slsci.2014.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Sleep complaints in the Brazilian population: Impact of socioeconomic factors

Abstract: National surveys are relevant for the study of sleep epidemiology since they can provide specific data about sleep in large dimension with important implications for the health system. Thus, the aim of this study was to investigate the prevalence of sleep complaints among the Brazilian population using a randomized cluster sample according to region and socioeconomic class. For this, a 3-stage sampling technique was used to randomly select Brazilian subjects of both genders older than 16 years. A total of 2017… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
2
9

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 34 publications
(47 reference statements)
3
25
2
9
Order By: Relevance
“…However, this "omnibus" survey excluded patients with restless legs syndrome and sleep apnea, thus possibly underestimating sleep-disorder prevalence. Hirotsu et al in a Brazilian population have found that sleep complaints increase with age, and there were more frequent in women findings similar to our results [14] .…”
Section: Discussionsupporting
confidence: 92%
“…However, this "omnibus" survey excluded patients with restless legs syndrome and sleep apnea, thus possibly underestimating sleep-disorder prevalence. Hirotsu et al in a Brazilian population have found that sleep complaints increase with age, and there were more frequent in women findings similar to our results [14] .…”
Section: Discussionsupporting
confidence: 92%
“…Persons with lower education level often face greater work-related stress, which may lead to insomnia symptoms. This study did not confirm previous findings that low income [ 40 ] was associated with insomnia symptoms.…”
Section: Discussioncontrasting
confidence: 99%
“…Thus, individuals with higher education levels may be more aware of the importance of sleep and of the conditions to increase its quality. Furthermore, unemployment and adverse socioeconomic conditions are strongly associated to insomnia 30 .…”
Section: Discussionmentioning
confidence: 99%